Peran Orang Tua dalam Menjaga Kesehatan Anak Akibat Masalah Kesehatan Gizi - Zahra Amelia; Mawar Sari; Fazrika Hummisyah; Vera Faujiah Siregar; Nur Ainun Dalimunthe; Jenny Maharani; Lafifah Balqis Lubis; Nazla Damia; Cindy Permatasari; Mai Astri Ananda (Lembaga Pengembangan Kinerja Dosen, 2026)
Malnutrition in children remains a serious public health challenge in Indonesia because it directly impacts growth, cognitive development, and the child's future quality of life. Parents play a crucial role in maintaining children's health, particularly in providing balanced nutrition and preventing nutritional problems such as stunting and malnutrition. This study aims to analyze the role of parents in maintaining children's health due to malnutrition based on a literature review. The method used is a qualitative literature study, through a search of various written sources in the form of scientific journals, articles, and relevant books obtained from Google Scholar. The results of the study indicate that the level of knowledge, education, parenting patterns, socioeconomic conditions, and active involvement of parents in monitoring children's growth significantly influence children's nutritional status and health. Parents play a role as providers of nutritious food, nutrition educators, role models of healthy lifestyles, and regular monitors of children's growth and development. Parents' lack of understanding of balanced nutrition, the habit of consuming instant foods, and minimal participation in health programs are risk factors for malnutrition in children. Therefore, increasing parental education and involvement through a family-based approach is an important strategy in efforts to prevent and address child nutrition problems sustainably.